EKSPLORASI WISATA, DAYA TARIK, DAN KEPUASAN PENGUNJUNG TERHADAP MINAT KUNJUNG DI PANTAI GUAMANIK - Firmansyah, Saputra Rizky; Ali (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine the effect of tourism facilities, attractions, and visitor satisfaction on the intention to revisit Guamanik Beach, Jepara. This study uses a quantitative approach to test the effect of tourism facilities, attractions, and visitor satisfaction on the intention to revisit. This study uses an explanatory or causal design, which aims to clarify the causal relationship between the independent variables (tourism facilities, attractions, visitor satisfaction) and the dependent variable (intention to revisit). This study involved 101 respondents who had previously visited Guamanik Beach. The researcher used a probability sampling technique with purposive sampling to select respondents. The data collection method used a questionnaire and data analysis used PLS-SEM with SmartPLS 3.0. The results showed that tourism facilities and visitor satisfaction had a significant effect on the intention to revisit. However, attractions did not have a significant effect. This study highlights the importance of tourism facilities and visitor satisfaction in building the intention to revisit. Guamanik Beach managers need to focus on improving facilities and service quality to increase visitor satisfaction. Although attractions do not have a significant effect, managers are still advised to highlight the uniqueness of this beach in promotions.